1989
DOI: 10.1111/j.1471-0528.1989.tb06307.x
|View full text |Cite
|
Sign up to set email alerts
|

2308 second trimester terminations using extra‐amniotic or intra‐amniotic prostaglandin E2: an analysis of efficacy and complications

Abstract: A total of 2308 mid-trimester terminations using PGE, extraamniotically (1608) or intra-amniotically (700) has been analysed for efficacy and immediate and early morbidity. 'The mean induction-toabortion intervals were similar for the two routes. Overall. 67% of the patients werc in hospital for 1 night. Morbidity rates were similar for the two administration routes and were no higher than those reported for second trimester terminations using dilatation and evacuation. Minor side-effects of vomiting occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…The mean induction-to-abortion interval in our patients was 21.3 h. This rate is within the range reported in the literature for induction-to-abortion interval of secondtrimester abortion using prostaglandins by various methods [1,3,7,8]. We performed Bumm curettage in 83.7%.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The mean induction-to-abortion interval in our patients was 21.3 h. This rate is within the range reported in the literature for induction-to-abortion interval of secondtrimester abortion using prostaglandins by various methods [1,3,7,8]. We performed Bumm curettage in 83.7%.…”
Section: Discussionmentioning
confidence: 56%
“…Hill and MacKenzie [1], who used PGE 2 extra-or intra-amniotically in 2,308 patients, observed in 60% gastrointestinal complications (diarrhea and vomiting) and fever. Hagar et al [8] and Chapman et al [7], who used PGE 2 as vaginal suppositories, reported these complications in 68 and 57%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der unvollständige Abort und die Plazentaretention sind bei der Prostaglandinanwendung relativ häufig registrierte Komplikationen und können teilweise schwere Infektionen zur Folge haben. Bei der extraamnialen Anwendung sind unvollständige Aborte in 25% [28] und Infektionen in bis zu 40% der Fälle [25] beschrieben worden. Die Rate unvollständiger Kürettagen nach D&C in unserer Gruppe ist mit 2,8% damit vergleichsweise sehr niedrig.…”
Section: Introductionunclassified
“…Nach intrazervikaler Prostaglandin-E 2 -Applikation sind Zervixverletzungen infolge des Primingeffekts sehr selten; Stampe Sorensen et al [33] und Herabutya und Israngura Na Ayudthaya [2] wiesen in ihren Untersuchungen keine Zervixverletzungen nach, Schmidt und Ditz [34] registrierten lediglich bei einer Patientin eine Läsion der Zervix. Zervixverletzungen wurden in Einzelfällen auch bei der extraamnialen Prostaglandin-E 2 -Applikation beschrieben [25,26,28,30,32,35]. Bei D&C hingegen resultieren Zervixverletzungen häufig aus einer forcierten und zu raschen Dilatation des Zervikalkanals mit Hegar-Stiften bei unreifer Portio oder -was in unserer Gruppe die Hauptursache war -aus dem Ausreissen der Kugelfasszangen.…”
Section: Introductionunclassified